Analysis of some aspects of staffing of healthcare system of the Republic of Kazakhstan - Omirbayeva, B.S. (BUKETOV BUSINESS REVIEW, 2017)
Modern high-quality and affordable health care is one of the conditions for successful development of society and the state. To fulfill this condition, it is necessary first of all to solve the problem of health security personnel. It is known that the quality of healthcare depends not only on the state of the material and technical base of public health, the adequacy of the organizational forms, but also on the security and availability of skilled workers. Therefore, this article analyzes the staffing of the health system in Kazakhstan. Analysis of the composition and structure of the medical personnel, trends in their numbers, their population security, the relationship between the specified categories, demographic characteristics are the main information basis for determining the needs of the community and the health system in the medical staff. In this regard, the article presents the data analysis by category of general practitioners, internists and pediatricians, who are one of the most important links in the primary health care (hereinafter - PHC), provided to the population. The analysis is performed on out-patient organizations in both the public sector and the private health sector. It is possible to refine the most vulnerable point in the problem of providing medical personnel in public health in Kazakhstan and to make some recommendations.